Pengaruh Praperlakuan Dingin Antera terhadap Pembentukan Kalus Cabai Merah Keriting (Capsicum annuum L.) Pretreatment on the Callus Formation of Curly Red Chilli Pepper (Capsicum annuum L.) - M Solin, Nida Wafiqah Nabila; Adriani, Dian; Zulfahmi, Zulfahmi; Irfan, Mokhamad; Rosmaina, Rosmaina (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
The production of the double haploid plant in vitro through anther culture technique is a plant breeding technique used to obtain pure strain rapidly. A variety of pretreatment has been reported to induce callus and regenerate planlets efficiently. This study aims at describing the influence of cold anther pretreatment towards the callus formation of curly red chili pepper (Capsicum annuum L.). This research was conducted in the laboratory of Genetics and Breeding, Faculty of Agriculture and Animal Science, Universtas Islam Negeri Sultan Syarif Kasim Riau. The explants used are anther of local genotype of curly red chili pepper. The anthers are stored at low temperatures (4 Â°c) with different time intervals of 0, 24, 48 and 72 hours. The results showed that the percentage of highest callus formation was obtained at 24 and 72 hours length storage, ie 50%. Cold pretreatment of 72 hours anther storage results in a faster callus with a percentage of the highest yellowish white callus color of 17.65% and a compact structure. The cold pretreatment with 72 hours anther storage is the most optimal acceleration in the development stage of anther culture and induces te formation of curly red chili pepper (Capsicum annuum L.) local genotypes.